Effect of Various Weed Management Practices on Pigeon Pea (Cajanus cajan L. Millsp.) - Moasunep; Singh, P. L.; Longkumer, L. Tongpang (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during the kharif season, 2011 to study how pigeon pea (Cajanus cajan L. Millsp.) respond to various weed management practices under foothills agro-climatic condition of Nagaland. Hand weeding at 20 and 40 DAS (T9) resulted in the lowest weed density (No. m-2), highest WCE (72.53%), lowest dry weight of weeds (15.33 g m-2) at 30 DAS. At 60 and 90 DAS, lowest dry weight of weeds (15 g m-2 and 32.00 g m-2) was noted with application of Imazethapyr @75 g a.i. ha-1+Quizalofop ethyl @ 50 g a.i. ha-1 on 15 DAS+1 hand weeding on 50 DAS/ Intercultivation. Hand weeding twice (20 and 40 DAS) produced better growth attributes viz. plant height (cm), shoot dry weight (g), number of branches measured 30, 60, 90, 120 DAS and at harvest; yield attributes viz. pod weight plant-1, number of seeds pod-1, 100 seed weight (g), seed yield (kg ha-1). Highest net return (` 30669.85 ha-1) and benefit:cost ratio (1.51) noticed when weeds were removed by hand weeding at 20 and 40 DAS (T9) compared to all the treatments under study.